ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada JNE Cabang Corolet, Daerah Tangerang Selatan) - Putri Nafra Berliana (2020)
This study uses quantitative descriptive methods conducted on JNE Corolet branch customers. The purpose of this study is to analyze and prove whether JNE Corolet Branch customer satisfaction is influenced by service quality and price. The population in this study is JNE Corolet Branch customers in South Tangerang area, Serua Indah Village, Ciputat District. The sample is 99 respondents JNE Corolet Branch customers using non-probability methods, purposive sampling. Data collection was carried out by distributing questionnaires to JNE Corolet Branch customers in the form of Google Forms. The analysis technique is using the Partial Least Square (PLS) method with Smart PLS 3.0 Software. The result showed that service quality has a significant effect on customer satisfaction. For the variable price does not significantly influence customer satisfaction.